The S-Domain Receptor Kinase Arabidopsis Receptor Kinase2 and the U Box/Armadillo Repeat-Containing E3 Ubiquitin Ligase9 Module Mediates Lateral Root Development under Phosphate Starvation in Arabidopsis. Issue 4 (25th June 2014) - Deb, Srijani; Sankaranarayanan, Subramanian; Wewala, Gayathri; Widdup, Ellen; Samuel, Marcus A.
Abstract : Autophagy plays an important role during lateral root development under phosphate starvation. Abstract: When plants encounter nutrient-limiting conditions in the soil, the root architecture is redesigned to generate numerous lateral roots (LR s) that increase the surface area of roots, promoting efficient uptake of these deficient nutrients. Of the many essential nutrients, reduced availability of inorganic phosphate has a major impact on plant growth because of the requirement of inorganic phosphate for synthesis of organic molecules, such as nucleic acids, ATP, and phospholipids, that function in various crucial metabolic activities. In our screens to identify a potential role for the S -domain receptor kinase1-6 and its interacting downstream signaling partner, the Arabidopsis ( Arabidopsis thaliana ) plant U box/armadillo repeat-containing E3 ligase9 (AtPUB9), we identified a role for this module in regulating LR development under phosphate-starved conditions. Our results show that Arabidopsis double mutant plants lacking AtPUB 9 and Arabidopsis Receptor Kinase2 ( AtARK2 ; ark2-1/pub9-1 ) display severely reduced LR s when grown under phosphate-starved conditions. Under these starvation conditions, these plants accumulated very low to no auxin in their primary root and LR tips as observed through expression of the auxin reporter DR5:: uidA transgene. Exogenous auxin was sufficient to rescue the LR developmental defects in the ark2-1/pub9-1 lines, indicating a requirement of auxin accumulation for this process. Our subcellular localization studies with tobacco ( Nicotiana tabacum ) suspension-cultured cells indicate that interaction between ARK2 and AtPUB9 results in accumulation of AtPUB9 in the autophagosomes. Inhibition of autophagy in wild-type plants resulted in reduction of LR development and auxin accumulation under phosphate-starved conditions, suggesting a role for autophagy in regulating LR development. Thus, our study has uncovered a previously unknown signaling module (ARK2-PUB9) that is required for auxin-mediated LR development under phosphate-starved conditions.